2016
DOI: 10.4155/fmc-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Trends of New Benzimidazole Derivatives

Abstract: Aim: In present study, the anti-inflammatory activities of a new series of benzimidazole derivatives were studied, investigating their inhibition of secretory phospholipase A2, lipoxygenase, COXs and lipopolysaccharide-induced secretion of TNF-α and IL-6 in mouse RAW264.7 macrophages. Results: Synthesized compounds effectively inhibited proinflammatory enzymes and cytokines. Conclusion: A strong inhibition of secretory phospholipases A2 was exhibited by benzimidazole derivatives with trifluoromethyl and methox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 47 publications
0
27
0
1
Order By: Relevance
“…Concerning 5‐LO, the analysis of the only one human protein structure (wild‐type) available in the Protein Data Bank (PDB code: 3O8Y), not co‐complexed with an inhibitor, disclosed a partially accessible ligand binding site, thus not compatible for the semi‐rigid molecular docking procedure. For these reasons, in this specific case, Induced Fit experiments should be performed and, considering the high number of compounds to be tested, this should require high computational times.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning 5‐LO, the analysis of the only one human protein structure (wild‐type) available in the Protein Data Bank (PDB code: 3O8Y), not co‐complexed with an inhibitor, disclosed a partially accessible ligand binding site, thus not compatible for the semi‐rigid molecular docking procedure. For these reasons, in this specific case, Induced Fit experiments should be performed and, considering the high number of compounds to be tested, this should require high computational times.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there are few studies reporting the synthesis of 2-aminobenzimidazole derivatives. A variety of benzimidazole-based compounds have shown their potential use as antidiabetic, anti-ulcer, anti-convulsant (Shingalapur, Hosamani, Keri, & Hugar, 2010), anti-infectious (Ozkay, Tunali, Karaca, & Isikdag, 2011), or anti-inflammatory (Bukhari et al, 2016) agents. Recent studies demonstrated that benzimidazole derivatives also exhibit anti-angiogenesis (Huang, Lien, Kuo, & Huang, 2012) and anti-tumour (Chu et al, 2015) properties.…”
Section: Introductionmentioning
confidence: 99%
“…We initially attempted the reactiono f2 -chloro-1H-benzo[d]imidazole with the in situ generated nitrile oxide,w hichw as pre-pared by the base-mediated dehydrochlorination of N-hydroximoyl chloride 1a.T he reactionw as carried out in the presence of organic and inorganic bases and in aprotic and protic solvents, such as EtOH, MeOH,t etrahydrofuran (THF), dichloromethane (DCM), N,N-dimethylformamide (DMF), isopropanol, 1,4-dioxane, and dimethylsulfoxide (DMSO,T able 1, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. At race amounto ft he desired compound 3a (Table 1, entries 3, 4, 10, and 11)w as formed by employing tetra-n-butylammonium fluoride (TBAF)o r4 -(N,N-dimethylamino)pyridine (DMAP)a sb ases (detected by high resolution HPLC-MS and 1 HNMR analysis).…”
Section: Resultsmentioning
confidence: 99%
“…Benzimidazoles and imidazoles are important molecular frameworks that are found in alkaloids, and compounds that contain these structuresg enerally have important biological activity, [1][2][3] including antitumor, [4][5][6] antimicrobial, [7,8] anti-inflammatory, [9,10] and antiviral properties. [11,12] Many commercial drugs also contain this moleculars keleton, such as protonp ump-inhibitors (e.g.,o meprazole) [13,14] and antihelmintics (e.g.,a lbendazole).…”
Section: Introductionmentioning
confidence: 99%